Ellie the flower girl - Barkley, Callie (Barkley, Callie. Critter Club, 2016)
"Ellie has always wanted to go to wedding, and her hopes finally come true when her cousin asks her to be a flower girl at her wedding. Then the Critter Club gets the cutest guest Ellie has ever seen: a little French bulldog. Ellie works hard to find a home for the puppy, but she's worried she won't be able to. Suddenly she has an idea that will guarantee that the puppy lives happily ever after!"--